Predicting judo champions and medallists using statistical modelling - Norjali Wazir, M. R. W.; Torfs, M.; Mostaert, M.; Pion, J.; Lenoir, M. (Archives of Budo, 2017)
Background and Study Aim: In the past decade, several studies have convincingly demonstrated that the identification of characteristics in young children can form a solid basis to identify those subjects with the most chance to excel at the international competition level. The present study aims to predict the performance of young male judo athletes with linear and non-linear predictive statistical models. It is hypothesized that a non-sport specific test battery will allocate athletes to their best achievement level at least three years past baseline.